2014
DOI: 10.1016/j.ultsonch.2013.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Thermosonication as a potential quality enhancement technique of apple juice

Abstract: Enzymatic browning and microbial growth lead to quality losses in apple products. In the present study, fresh apple juice was thermosonicated using ultrasound in-bath (25 kHz, 30 min, 0.06 W cm(-3)) and ultrasound with-probe sonicator (20 kHz, 5 and 10 min, 0.30 W cm(-3)) at 20, 40 and 60°C for inactivation of enzymes (polyphenolase, peroxidase and pectinmethylesterase) and microflora (total plate count, yeast and mold). Additionally, ascorbic acid, total phenolics, flavonoids, flavonols, pH, titratable acidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
143
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(186 citation statements)
references
References 46 publications
34
143
1
1
Order By: Relevance
“…For raw juice and pasteurized juice, the pH values were recorded as 3.73 ± 0.04 and 3.68 ± 0.04, respectively (Table ). Similar findings were reported by several researchers (Abid et al, ; Cruz‐Cansino et al, ; Nayak et al, ).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…For raw juice and pasteurized juice, the pH values were recorded as 3.73 ± 0.04 and 3.68 ± 0.04, respectively (Table ). Similar findings were reported by several researchers (Abid et al, ; Cruz‐Cansino et al, ; Nayak et al, ).…”
Section: Resultssupporting
confidence: 91%
“…The addition of hydroxyl group to the aromatic ring as a result of sonication may also be the reason for increasing the TPC levels in thermosonicated juices (Bhat et al, ; Jabbar et al, ). The TPC levels of thermosonicated juices were also increased as the treatment time increased and it can be observed from the results given in Tables and it was supported by various studies (Abid et al, ; Bhat et al, ; Guerrouj et al, ).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…There was a slow decrease in PME as frequency increased and time decreased exceeding the midpoint (Figure c). Similar findings have been indicated (Abid et al, ; Raviyan, Zhang, & Feng, ).…”
Section: Resultssupporting
confidence: 90%
“…Abid et al (2014), observed 47% PPO RA reduction when increasing the TS temperature from 40 to 60°C for a 10 min sonication process (0.30 W/mL). For PPO in mushroom crude extract, an increase from 55 to 65°C TS temperature (0.43 W/mL) for a 10 min process, reduced the PPO RA by 67% .…”
Section: Resultsmentioning
confidence: 92%